2021
DOI: 10.5222/buchd.2021.94715
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis in the Field of Pediatric Anesthesia and Turkey’s Contribution to Research

Abstract: Objective: Bibliometric analysis can be used to assess the contributions of scholars, institutions, countries by examining the materials published in a certain discipline. The objective of this study is to make a bibliometric analysis in the field of pediatric anesthesia and to examine Turkey’s contribution to research in this field. Methods: I used the search engine of the Web of Science (WoS), and included all types of contributions (original articles, reviews, letters, editorials, etc.) in the bibliometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…British Journal of Education is a journal with a very high impact factor (11.719 for 2021), which publishes four issues a year from the UK. In our study, the journals that we have determined to have the most cited publications on pediatric caudal anesthesia are the journals that have been included in the list of the most cited journals in similar bibliometric analysis studies conducted on different subjects in the field of anesthesia (18,20,29,30). They are among the most productive journals in this research field for the following reasons: their impact factors, their publication history spanning many years, and their inclusion in this and similar bibliometric analysis studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…British Journal of Education is a journal with a very high impact factor (11.719 for 2021), which publishes four issues a year from the UK. In our study, the journals that we have determined to have the most cited publications on pediatric caudal anesthesia are the journals that have been included in the list of the most cited journals in similar bibliometric analysis studies conducted on different subjects in the field of anesthesia (18,20,29,30). They are among the most productive journals in this research field for the following reasons: their impact factors, their publication history spanning many years, and their inclusion in this and similar bibliometric analysis studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are bibliometric analysis studies on some methods, some types of diseases, and medical education in medicine (10)(11)(12)(13)(14)(15)(16)(17). In the field of anesthesia, in bibliometric analysis studies, it was observed that subjects such as studies in the field of anesthesia, anesthesia applications in different age groups, and regional anesthesia were discussed in bibliometric analysis studies (18)(19)(20)(21). There was no study involving bibliometric analysis of studies on pediatric caudal anesthesia.…”
Section: Introductionmentioning
confidence: 99%